Dakwah Map of Surau Baitul Quddus Pueh, Sematan, Malaysia - Asrul Asrul; Sapriadi Sapriadi; Sodikin Sodikin; Tasya Tasya; Paisal Paisal; Nurul Hidayat; Ahmad Zabidi; Manja Manja; Deni Irawan; Sabari Sabari; Beti Yanuri Posha; Rifqi Muhammad (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
This is a report of service to the community. The purpose of this writing is to briefly describe the preaching map of Surau Baitul Quddus Pueh, Sematan Malaysia. The reporting procedure uses a qualitative-descriptive approach. Data collection techniques are done by using interviews, observations, and documentation. The location of this research was carried out at Surau Baitul Quddus Pueh, Sematan Malaysia, in 2023. This research uses The results of this research show that Kampung Pueh has a surau named Surau Baitul Quddus, which was established on August 26, 2018, and the existing facilities and infrastructure in Surau Baitul Quddus Pueh are more or less the same as the surau in general.